The Senior Companion Program Plus: A culturally tailored psychoeducational training program (innovative practice). (February 2020) - Fields, Noelle L; Xu, Ling; Richardson, Virginia E; Parekh, Rupal; Ivey, Dorothea; Feinhals, Gretchen; Calhoun, Melanie
A purposive sample of African American Senior Companions ( N  = 23) participated in a 5-day, 20-hour psychoeducational training designed to address the unique cultural needs of African American dementia caregivers. Previous studies have not utilized lay caregiver volunteers such as Senior Companions in dementia research in the United States. Pre- and post-tests were administered to determine whether African American Senior Companions increased their knowledge of Alzheimer's disease after participating in the Senior Companion Program Plus. Results from both the quantitative and qualitative data suggest that participants improved their understanding of Alzheimer's disease. Findings from the Senior Companion Program Plus pilot warrant further study for its potential as cost effective, culturally tailored training for Senior Companions who serve persons with dementia and their family caregivers.